Safety and efficacy of lenvatinib combined with camrelizumab plus transcatheter arterial chemoembolization for unresectable hepatocellular carcinoma: A two-center retrospective study - Sun, Bo; Zhang, Lijie; Sun, Tao; Ren, Yanqiao; Cao, Yanyan; Zhang, Weihua; Zhu, Licheng; Guo, Yusheng; Gui, Yuxi; Liu, Fengyong; Chen, Lei; Xiong, Fu; et al. (Frontiers in Oncology, 2022)
Objectives To compare the safety and efficacy of lenvatinib (LEN) combined with camrelizumab plus transcatheter arterial chemoembolization (TACE-LEN-C) and TACE combined with LEN (TACE-LEN) in patients with unresectable hepatocellular carcinoma (uHCC). Methods Eighty-three patients with uHCC treated with TACE-LEN-C or TACE-LEN from September 2018 to May 2021 were enrolled in this retrospective study. Overall survival (OS), progression-free survival (PFS), local tumor response, and adverse events (AEs) were evaluated. Univariate and multivariate analyses were used to determine the factors affecting survival. Results There were 31 patients in the TACE-LEN-C group and 52 patients in the TACE-LEN group. The median follow-up period was 14.2 months (range 7.2–25.2 months) in the whole study. The combination of triple therapy was found to significantly prolong the PFS (12.5 months vs. 6.6 months, P<0.001) and OS (18.9 months vs. 13.9 months, P<0.001. In terms of tumor response, the combination demonstrated a higher objective response rate (71% vs. 42.3% by the modified Response Evaluation Criteria in Solid Tumors, P=0.023) without a statistically significant difference in the disease control rate (93.5% in TACE-LEN-C, 80.8% in TACE-LEN, P=0.195). In the multivariate analysis, two independent factors affecting PFS were identified: number of tumors and treatment. Three independent factors affected OS: number of tumors, Barcelona Clinic Liver Cancer (BCLC) stage, and treatment. All the AEs were tolerable. Conclusion TACE-LEN-C is a safe and effective treatment for patients with uHCC, and could be a potential treatment option.